PENERAPAN MATEMATIKA EKONOMI MELALUI KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Oktasari Putri, Prihastini; Febriana, Rina; Anggreini Sarumaha, Yenny; Marice Inda, Yohana; Yunita Sari, Tri; Nur Azizah, Qoirina; Meliana Isti, Desfanti (Jurnal Abdimas Musi Charitas, 2024)
This community service project aims at providing an assistance towards Proyek Penguatan Profil Pelajar Pancasila (P5) at Bina Jaya Junior High School in Banguntapan. The chosen theme in this activity was sustainable lifestyles associated with economic mathematics by utilizing recycled materials. Some problems behind this community service activity included the lack of school readiness in managing P5 activities, inadequate understanding of teachers related to the Kurikulum Merdeka, and limited school budgets. To address these issues, the current community service activity was conducted involving teachers and students in theme namely a sustainable lifestyles project that utilizes recycled materials. The activity follows the Classroom Action Research (CAR) method, consisting of three stages: action plan, observation and evaluation, and reflection. After finishing the project, there have been a successful improvement in the understanding of school management; teachers and students’s concepts about P5 in Kurikulum Merdeka, as well as the integration of economic mathematics concepts into creative projects. Some examples were crafting plants’ vases from recycled materials, creating organic fertilizers, and planting aloe vera (Aloe vera) and butterfly pea flowers (Clitoria ternatea). The results indicate the improvement in understanding the concept of economic mathematics and increasing students’ skills in applying them in a sustainability lifestyle context. Supporting P5 activity with an economic mathematics approach can strengthen students' characters, support the Kurikulum Merdeka, and provide practical insights into economic aspects relevant to daily life.